2000
DOI: 10.1042/cs19990362
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C modifies the cardiovascular and microvascular responses to cigarette smoke inhalation in man

Abstract: Both neutrophil margination and increases in the non-invasively assessed parameter, isovolumetric venous congestion cuff pressure (Pv(i)), are symptomatic of some inflammatory diseases. Neutrophil margination occurs primarily, though not exclusively, at the post-capillary endothelial surface. The local haemodynamic changes resulting from margination may be responsible for the observed increases in Pv(i). Smoke inhalation has been shown in animal studies to cause an increase in post-capillary neutrophil margina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The size of this effect was in accordance with other studies reporting an effect of acute smoking on heart rate [5,6,[29][30][31]. The observed increase in systolic blood pressure after acute smoking is also in accordance with other studies [7][8][9][10].…”
Section: Discussionsupporting
confidence: 94%
“…The size of this effect was in accordance with other studies reporting an effect of acute smoking on heart rate [5,6,[29][30][31]. The observed increase in systolic blood pressure after acute smoking is also in accordance with other studies [7][8][9][10].…”
Section: Discussionsupporting
confidence: 94%
“…The results indicated that early supplementation with these vitamins was associated with a decrease in the development of pre-eclampsia. Reactive oxygen species induce neutrophil margination, an effect that is blocked by vitamin C [29]. These data suggest that neutrophil margination may contribute to the endothelial dysfunction of pre-eclampsia.…”
Section: Discussionmentioning
confidence: 87%
“…In these studies, the data showed no differences in CFC, P vi and, therefore, the value of J vL . This implies that the tissue had regained its equilibrium state during the 30 min rest phase [33].…”
Section: Discussionmentioning
confidence: 99%